2017
DOI: 10.1002/er.3903
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Ce0.9 Cu0.1 O2 /activated carbon as highly active and stable HI decomposition catalyst

Abstract: Summary Effects of additives to Pt‐CeO2/activated carbon (M563) catalysts on HI decomposition were studied. Among the additives studied, it was found that the addition of Cu to Pt‐CeO2 is the most effective for increasing the catalytic activity to HI decomposition. On this catalyst, almost the equilibrium hydrogen iodide (HI) conversion was achieved at temperature higher than 573 K. Cu addition increased Pt dispersion by anchoring effects. Therefore, in spite of decreased Brunauer‐Emmett‐Teller surface area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It is reported that the coexistence of water shows negative effects on HI decomposition and so HI decomposition on Pt‐Rh/TiO 2 /M563 catalyst was measured under coexistence of H 2 O. Figure shows temperature dependence of HI conversion under dry and coexistence of H 2 O (25 vol%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the coexistence of water shows negative effects on HI decomposition and so HI decomposition on Pt‐Rh/TiO 2 /M563 catalyst was measured under coexistence of H 2 O. Figure shows temperature dependence of HI conversion under dry and coexistence of H 2 O (25 vol%).…”
Section: Resultsmentioning
confidence: 99%
“…Advantage of metal oxide‐supported Pt is high stability; however, the activity is still not high enough. In our previous study, we found that Pt/Ce(Cu)O 2 /activated carbon is highly active to HI decomposition (almost the equilibrium conversion) as well as high stability over 100 hours . However, from the equilibrium, CeO 2 has reactivity with I 2 resulting in a decreased HI conversion.…”
Section: Introductionmentioning
confidence: 98%
“…The influence of operating temperature on the electrolytic performance was analyzed in two opposite aspects. First, increase in temperature enhances the activity of species in the solution and increases the reaction kinetic rate because of the endothermic characteristic of HI decomposition . On contrary, the rising temperature reduces the local current density according to Equation .…”
Section: Resultsmentioning
confidence: 99%
“…And excess H 2 O is also necessary for making the Bunsen reaction more thermodynamically favorable . As a result, the practical excess amounts of I 2 and H 2 O with respect to their stoichiometric value usually reach 4 to 6 and 11 to 13 according to Lee et al The produced light H 2 SO 4 phase (most H 2 SO 4 , H 2 O and less HI, I 2 ) and the heavy HIx phase (most HI, I 2 , H 2 O and less H 2 SO 4 ) require liquid phase separation and purification before the catalytic decomposition of H 2 SO 4 and HI . A large amount of energy is required to remove and recycle the excess iodine and water after liquid phase separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation